Ogfod1 deletion increases cardiac beta-alanine levels and protects mice against ischaemia– reperfusion injury . Issue 13 (20th October 2021) - Harris, Michael; Sun, Junhui; Keeran, Karen; Aponte, Angel; Singh, Komudi; Springer, Danielle; Gucek, Marjan; Pirooznia, Mehdi; Cockman, Matthew E; Murphy, Elizabeth; Kennedy, Leslie M
Abstract: Aims: Prolyl hydroxylation is a post-translational modification that regulates protein stability, turnover, and activity. The proteins that catalyze prolyl hydroxylation belong to the 2-oxoglutarate- and iron-dependent oxygenase family of proteins. 2-oxoglutarate- and iron-dependent oxygenase domain-containing protein 1 (Ogfod1), which hydroxylates a proline in ribosomal protein s23 is a newly described member of this family. The aims of this study were to investigate roles for Ogfod1 in the heart, and in the heart's response to stress. Methods and results: We isolated hearts from wild-type (WT) and Ogfod1 knockout (KO) mice and performed quantitative proteomics using tandem mass Tag labelling coupled to liquid chromatography and tandem mass spectrometry (LC-MS/MS) to identify protein changes. Ingenuity pathway analysis identified 'Urate Biosynthesis/Inosine 5′-phosphate Degradation' and 'Purine Nucleotides Degradation II (Aerobic)' as the most significantly enriched pathways. We performed metabolomics analysis and found that both purine and pyrimidine pathways were altered with the purine nucleotide inosine 5′-monophosphate showing a 3.5-fold enrichment in KO hearts ( P = 0.011) and the pyrimidine catabolism product beta-alanine showing a 1.7-fold enrichment in KO hearts ( P = 0.014). As changes in these pathways have been shown to contribute to cardioprotection, we subjected isolated perfused hearts to ischaemia and reperfusion (I/R). KO hearts showed a 41.4% decrease in infarct size and a 34% improvement in cardiac function compared to WT hearts. This protection was also evident in an in vivo I/R model. Additionally, our data show that treating isolated perfused WT hearts with carnosine, a metabolite of beta-alanine, improved protection in the context of I/R injury, whereas treating KO hearts with carnosine had no impact on recovery of function or infarct size. Conclusions: Taken together, these data show that Ogfod1 deletion alters the myocardial proteome and metabolome to confer protection against I/R injury. Graphical Abstract: